Faktor-Faktor Yang Mempengaruhi Pengetahuan Gizi Pada Ibu Balita Gizi Buruk - Ayi Tansah Rohaeti (Akademi Kebidanan La Tansa Mashiro, 2014)
The purpose of research is to determine the extent of knowledge about nutrition in the mother Toddler Malnutrition. The method used is descriptive analytic method with cross-sectional approach. Based on the results of samples taken from the entire population of 70 mothers who have children malnutrition obtained mostly low nutritional knowledge of as many as 42 (60%) and that have a high knowledge of 28 (40%). The test results are statistically significant relationship between the level of education, maternal employment status, and income families with a mother's knowledge. And there is no significant relationship between age and number of children with a mother's knowledge.